Investigating Senior and Middle Level Leaders’ Perceptions of the Implementation of School Inspection Models in Selected Dubai and Northern Emirates Private Schools - EZZELDIN, ESMAT (2023)
Research has shown that school inspection is one of the most important tools that can be used to track and ensure the quality of education provided to students is at the expected level. The United Arab Emirates (UAE) has, in the past few years, initiated several policies to raise the quality of education. The UAE Vision 2030 lays specific attention on raising the educational quality of its residents, hence raising the human productivity and efficiency of the future workforce. As a result, several initiatives and projects have been implemented to monitor the quality of education in schools. One of them is the foundation of quality assurance entities that supervise and oversee the educational process through different inspection models. However, different stakeholders have various perceptions of the effectiveness of these initiatives to achieve quality education. In view of this, the main aim of this study is to investigate senior and middle leaders’ perceptions of the implementation of the school inspection models in selected private schools. The theoretical framework of the thesis is based on the following theories: Taylors’ Scientific Management Theory; School Inspection Effects and Causal Mechanism Model; School Inspection Effects and Effectiveness Model; and School Inspection Outcome Model. A sequential mixed method is used to facilitate the research process. Document analysis, questionnaires, and interviews were used to collect data from senior and middle leaders in the selected private schools. The research findings identify and classify the models of school inspection that are implemented. The findings also show that school inspection models have a significant role in supporting school leadership in school improvement and continuous development; however, the findings also show that school inspection could lead to some unintended consequences, such as some schools showing activities they have never done before or focusing on the quantity of policies and practices more than their quality. The study provides a set of recommendations about how to improve school inspection models based on the best practices implemented that led to the desired outcomes such as the implementation of monitoring and development visits that guide schools on how to address the recommendations received from full inspections.